Understanding the Barrier Layer Formed via Adding BTAH in Copper Film Electrodeposition. Issue 2 (1st January 2019) - Chang, Tingru; Leygraf, Christofer; Wallinder, Inger Odnevall; Jin, Ying
Abstract : The influence of surface adsorption of benzotriazole (BTAH) and of chloride ions (Cl − ) on the kinetics of copper electrodeposition/dissolution in copper sulfate solutions and on copper deposit characteristics have been investigated using electrochemical quartz crystal microbalance (EQCM) combined with cyclic voltammetry (CV). The addition of BTAH alone increases the overpotential of copper deposition, whereas a Cu(I)BTA complex forms at potentials higher than 0.08 V (vs. SCE) accompanied with the occurrence of copper anodic dissolution. With simultaneous addition of BTAH and Cl −, surface adsorption of Cl − competes with that of BTAH during the initial stage of copper nucleation. Different cuprous reaction intermediates form in the examined potential range −0.4 to 0.3 V (vs. SCE), which partly eliminate the favorable effect of BTAH on the deposited copper. A BTAH-containing adsorbed layer formed on the matte side of electrodeposited copper film in the presence of BTAH with or without Cl −, exhibiting a barrier surface property and an improved corrosion resistance compared with the copper film electrodeposited in the electrolyte without addition of BTAH.